The invasive alien species Bidens pilosa (Asteraceae) has successfully invaded and acclimated to coastal areas - Endo, Uta; Shiba, Masayuki; Fukuda, Tatsuya (Frontiers in Conservation Science, 2025)
The invasion of plants into specialized environments requires acclimatory changes, which can simultaneously act as barriers to further invasion in these contexts. In coastal areas, vegetation is shaped by various stresses from the marine environment; therefore, these areas are predominantly inhabited by plant species that have evolved specific acclimations to these stresses, including many endemic species. In recent years, the invasive species Bidens pilosa L. (Asteraceae) has been reported in the coastal areas of Japan. We conducted comparative morphological analyses of coastal and inland populations of B. pilosa to elucidate the background of their acclimation to coastal areas. The large leaf area of B. pilosa is suggested to be involved in the capture of sand blown by the wind in the unstable soil composed of sea sand in its habitat. In addition, the acclimatory changes in B. pilosa were achieved without considerable alterations in the resource allocation ratio between stems and leaves. The coastal population of B. pilosa exhibited a significantly higher ratio of resources allocated to roots, indicating that this acclimationfacilitated stable establishment in coastal soils and enhanced moisture acquisition in coastal areas subjected to severe drought stress. In contrast to the increased ratio of resource allocation to roots, the coastal population of B. pilosa displayed a significantly lower investment in inflorescences. The findings suggest that once a population is established, it can sustain itself with minimal investment in inflorescences. This is likely attributable to the limited number of plants in coastal areas and reduced competitive pressures in these environments. These acclimatory changes in B. pilosa may lead to the expansion of its habitat in various coastal areas.